SOCIO-ECONOMIC LIFE OF THE SUGDIANS IN SOURCES IN THE SUGDIAN LANGUAGE - Sattorov Eldor Bobir ugli; Babalova Dilafruz Asadovna (Web of Journals Publishing, 2024)
An integral part of the history of Uzbekistan, the attention to the study of the history of the Sughd confederation is increasing. After all, in the early Middle Ages, Sughd occupied an important place in the development of the Central and Far Eastern regions. This situation is closely related to Sughd's favorable geographical location, active participation in international trade, economic relations, and high level of social life.
Keywords: the archive documents of Mugh Mountain, the texts of the palace report (input, output), Panjikent palace, documents No. 6, A-5, A-11, V-9.